Seeking the Light in Intensive Care Unit Sedation: The Optimal Sedation Strategy for Critically Ill Patients - Gitti, Nicola; Renzi, Stefania; Marchesi, Mattia; Bertoni, Michele; Lobo, Francisco A.; Rasulo, Frank A.; Goffi, Alberto; Pozzi, Matteo; Piva, Simone (Frontiers in Medicine, 2022)
The clinical approach to sedation in critically ill patients has changed dramatically over the last two decades, moving to a regimen of light or non-sedation associated with adequate analgesia to guarantee the patient’s comfort, active interaction with the environment and family, and early mobilization and assessment of delirium. Although deep sedation (DS) may still be necessary for certain clinical scenarios, it should be limited to strict indications, such as mechanically ventilated patients with Acute Respiratory Distress Syndrome (ARDS), status epilepticus, intracranial hypertension, or those requiring target temperature management. DS, if not indicated, is associated with prolonged duration of mechanical ventilation and ICU stay, and increased mortality. Therefore, continuous monitoring of the level of sedation, especially when associated with the raw EEG data, is important to avoid unnecessary oversedation and to convert a DS strategy to light sedation as soon as possible. The approach to the management of critically ill patients is multidimensional, so targeted sedation should be considered in the context of the ABCDEF bundle, a holistic patient approach. Sedation may interfere with early mobilization and family engagement and may have an impact on delirium assessment and risk. If adequately applied, the ABCDEF bundle allows for a patient-centered, multidimensional, and multi-professional ICU care model to be achieved, with a positive impact on appropriate sedation and patient comfort, along with other important determinants of long-term patient outcomes.